2013
DOI: 10.1016/j.cemconcomp.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbonation of calcareous composites: Influence of curing

Abstract: This paper reports the effect of curing on the susceptibility of cementitious composites to carbonation using supercritical carbon dioxide. Samples made using a compression moulding technique were cured in water before and/or after carbonation and the effect on porosity, microstructure, solid phase assemblage and flexural strength was determined. In terms of development of mechanical strength, no benefit was gained from any period of pre-or post-carbonation curing regime. Yet samples cured prior to carbonation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Early carbonation contributes to decrease these voids around the cellulose fibers. Farahi et al [35,36] also observed very little porosity at the interface between aggregate particles and groundmass when composites were submitted to supercritical carbonation. Santos et al [25] observed changes in the nanostructure in the vicinity of the fiber by energy-dispersive X-ray spectroscopy maps in extruded cement-based composite after early supercritical carbonation and before accelerated aging.…”
Section: Resultsmentioning
confidence: 92%
“…Early carbonation contributes to decrease these voids around the cellulose fibers. Farahi et al [35,36] also observed very little porosity at the interface between aggregate particles and groundmass when composites were submitted to supercritical carbonation. Santos et al [25] observed changes in the nanostructure in the vicinity of the fiber by energy-dispersive X-ray spectroscopy maps in extruded cement-based composite after early supercritical carbonation and before accelerated aging.…”
Section: Resultsmentioning
confidence: 92%
“…It seems that, in early hydration stages, the C-S-H becomes intermingled with carbonates, generating an amorphous calcium-silicatehydrocarbonate binding phase [116], while CH is converted to CaCO3 [109]. In fact, effects responsible for marked strength gain probably include subtle changes in C-S-H microstructure, not only simple pore filling by CaCO3 as often stated [121,122].…”
Section: Accelerated Carbonation Curingmentioning
confidence: 99%
“…Apparently, the carbonaceous aggregate providedas opposed to quartz sanda surface for the crystallization of carbonate phases during treatment, thus improving the connection between the aggregate particles and the hardened cement paste matrix at the contact zone. Farahi et al [18] also noted an increase in the flexural strength of mortar specimens with calcitic aggregate after scCO2 treatment. In earlier investigations [20], it has been found that an increase in the strength of hardened cement paste specimens with w/c = 0.6 can be produced after a 48 hour treatment at only 3 bar and 20 °C.…”
Section: Carbonation Depth MMmentioning
confidence: 89%
“…Short et al [14] have noted that the relative humidity during the preliminary storage of hardened cement paste specimens affects the treatment process with scCO2, the most favourable relative humidity for storage before scCO2 treatment being about 35 % for maximum phase changes. In addition, positive effects of scCO2 treatment on strength are reported for cement-bonded glass fibres [16], wood fibreboard [17] and specimens with a cement-lime binder produced by pressing [18].…”
Section: Introductionmentioning
confidence: 97%